Simple simon says game using arduino / Muhammad Fakhroul Rodhi Suid & Arif Anwar Abdul Karim - Suid, Muhammad Fakhroul; Abdul Karim, Arif Anwar (2015)
Simon Says ( or Simple Simon Says) is a child's game for 3 or more players where 1 player takes the role of "Simon" and issues instructions (usually physical actions such as "jump in the air" or "stick out your tongue") to the other players, which should only be followed if prefaced with the phrase "Simon says", for example, "Simon says, jump in the air". Players are eliminated from the game by either following instructions that are not immediately preceded by the phrase, or by failing to follow an instruction which does include the phrase "Simon says". It is the ability to distinguish between ugly and pretty commands, rather than physical ability, that usually matters in the game; in most cases, the action just needs to be attempted. The object for the player acting as Simon is to get all the other players out as quickly as possible; the winner of the game is usually the last player who has successfully followed all of the given commands. Occasionally however, 2 or more of the last players may all be eliminated by following a command without "Simon Says", thus resulting in Simon winning the game. The game is well embedded in popular culture, with numerous references in films, music and literature.